2019
DOI: 10.1177/0007650319873654
|View full text |Cite
|
Sign up to set email alerts
|

The Global Diffusion of Supply Chain Codes of Conduct: Market, Nonmarket, and Time-Dependent Effects

Abstract: Why and how have supply chain codes of conduct diffused among lead firms around the globe? Prior research has drawn on both institutional and stakeholder theories to explain the adoption of codes, but no study has modeled adoption as a temporally dynamic process of diffusion. We propose that the drivers of adoption shift over time, from exclusively nonmarket to eventually market-based mechanisms as well. In an analysis of an original data set of more than 1,800 firms between the years 2006 and 2015, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 103 publications
(143 reference statements)
1
11
0
Order By: Relevance
“…At the same time, issues that were salient in prior periods also continued to attract significant attention. This period saw a strengthening of research concerned with climate change and environmental issues (Backman et al, 2017; Delmas & Lessem, 2017; Rekker et al, 2021), and significant attention to ethical issues in the context of supply chains (Allet, 2017; Altura et al, 2021; Egels-Zandén, 2017). There was also a considerable amount of research on CSR in SMEs, corporate reputation, and bottom of the pyramid markets, in part reinforced by special issues or sections of the journals that encouraged attention to these issues.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, issues that were salient in prior periods also continued to attract significant attention. This period saw a strengthening of research concerned with climate change and environmental issues (Backman et al, 2017; Delmas & Lessem, 2017; Rekker et al, 2021), and significant attention to ethical issues in the context of supply chains (Allet, 2017; Altura et al, 2021; Egels-Zandén, 2017). There was also a considerable amount of research on CSR in SMEs, corporate reputation, and bottom of the pyramid markets, in part reinforced by special issues or sections of the journals that encouraged attention to these issues.…”
Section: Resultsmentioning
confidence: 99%
“…They found that, when responding to pressures associated with values of fair treatment of employees, the use of tailored rather than standardised CSR approaches helped firms to strengthen relationships with their employees. Similarly, other studies have assessed firms’ responses to pressures from governments (e.g., Luo et al., 2017), NGOs and labour groups (e.g., Altura et al., 2021), and societal stakeholders in general (e.g., Helmig et al., 2016).…”
Section: Looking Back: the Role Of Values In Institutional Theory‐bas...mentioning
confidence: 99%
“…For example, Höllerer (2013) investigated the diffusion of CSR in Austria and the role of institutional pressures vis‐à‐vis the social position of actors for CSR dissemination within national borders. Other studies have focused on the nature of diffusion, either by examining its complexity (Raffaelli & Glynn, 2014) or temporal dimension (Altura et al., 2021).…”
Section: Looking Back: the Role Of Values In Institutional Theory‐bas...mentioning
confidence: 99%
“…For instance, visiting a supplier’s operations can enable buyers to confront a supplier’s code of conduct with the social responsibility practices it adopts in its daily operations (New, 2015). Although suppliers’ codes of conduct shift over time (Altura et al , 2019), visiting suppliers’ plants helps avoid modern slavery, particularly in first-tier suppliers (Stevenson and Cole, 2018; Cho et al , 2019). While visiting these plants enables illegal acts such as modern slavery to be detected, third-party monitors, who are widely employed for detecting supplier misconduct, can also be used as a remedy for dealing with criminal behavior (Stevenson and Cole, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The firm’s ethical responsibilities might also reflect honor and respect for the moral rights of customers, suppliers, employees, communities and other stakeholders. In the supply chain, it can include, for example, compliance with sourcing within particular codes of conduct (Roberts, 2003; Asif et al , 2019; Altura et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%